2016
DOI: 10.1128/aem.02517-15
|View full text |Cite
|
Sign up to set email alerts
|

A Branch Point of Streptomyces Sulfur Amino Acid Metabolism Controls the Production of Albomycin

Abstract: c Albomycin (ABM), also known as grisein, is a sulfur-containing metabolite produced by Streptomyces griseus ATCC 700974. Genes predicted to be involved in the biosynthesis of ABM and ABM-like molecules are found in the genomes of other actinomycetes. ABM has potent antibacterial activity, and as a result, many attempts have been made to develop ABM into a drug since the last century. Although the productivity of S. griseus can be increased with random mutagenesis methods, understanding of Streptomyces sulfur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Also, the cystathionine-γ-lyase ( cysA ) contributes to cysteine formation (Additional file 1: Figure S5B). However, the genes SCLAV_5668, encoding a cystathionine-γ-synthase, and SCLAV_p1477, encoding a cysteine synthase, do not exist in S. clavuligerus pSCL4-; in addition, a gene homologous to metC, for a cystathionine β-lyase [ 35 ] has not been detected in S. clavuligerus genome . Sulfur metabolism in Streptomyces is still poorly understood, and more biochemical studies are required to know relationship between genes and enzymes and regulatory mechanisms in Streptomyces cysteine-methionine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cystathionine-γ-lyase ( cysA ) contributes to cysteine formation (Additional file 1: Figure S5B). However, the genes SCLAV_5668, encoding a cystathionine-γ-synthase, and SCLAV_p1477, encoding a cysteine synthase, do not exist in S. clavuligerus pSCL4-; in addition, a gene homologous to metC, for a cystathionine β-lyase [ 35 ] has not been detected in S. clavuligerus genome . Sulfur metabolism in Streptomyces is still poorly understood, and more biochemical studies are required to know relationship between genes and enzymes and regulatory mechanisms in Streptomyces cysteine-methionine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a single replacement of the sulfur with oxygen resulted in the complete loss of antibacterial activity, suggesting a critical role of the sulfur atom in the activity of albomycins. A biosynthetic approach has also been attempted for the generation of albomycin analogs 23 , but albomycin production by S. griseus is difficult and has yet to be scaled up efficiently 24 . Herein, we describe the total synthesis of the three natural albomycins ( 1a – c ), which features a Pummerer reaction for nucleobase introduction and an aldol reaction to expand the side chain of thionucleoside.…”
Section: Introductionmentioning
confidence: 99%
“…13 The gene abmD in the abm gene cluster encodes another PLP-dependent enzyme, although it does not show high sequence similarity to known racemases/epimerases. While it has been reported that overexpression of abmD increases the level of 1 production, 14 the catalytic role of the gene product AbmD has not been characterized. To determine whether AbmD can catalyze the epimerization of the AbmH-product 28 (or its physiological equivalent), N -His 6 -tagged AbmD was heterologously overexpressed and purified from E. coli (Figure S2).…”
mentioning
confidence: 99%